1991
DOI: 10.1136/jmg.28.7.490
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossia-hypodactyly syndrome with hydrocephalus: a clue to the aetiology?

Abstract: Case report This female infant was the third child of healthy, unrelated parents. The mother's second pregnancy ended at 30 weeks with the birth of a baby with left heart hypoplasia who survived a few days. The current pregnancy was uncomplicated until the birth at 36 weeks of a stillborn female baby with multiple malformations (fig 1). Birth weight was 2400 g, length was 46 cm, and head circumference 32 cm. Clinical examination showed a proportionate large head with wide fontanelles. There were reduction anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Hypoglossia-hypodactylia syndrome is a difficult disease to treat because the method of forming the tongue to make it functional has not been established. There are many reports of hypoglossia-hypodactylia syndrome [1][2][3][4][5], but the extent of hypoplasia of the tongue and limbs varies. Hypoglossia-hypodactylia syndrome has been classified by Hall as oromandibular and limb hypogenesis syndromes [1].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglossia-hypodactylia syndrome is a difficult disease to treat because the method of forming the tongue to make it functional has not been established. There are many reports of hypoglossia-hypodactylia syndrome [1][2][3][4][5], but the extent of hypoplasia of the tongue and limbs varies. Hypoglossia-hypodactylia syndrome has been classified by Hall as oromandibular and limb hypogenesis syndromes [1].…”
Section: Discussionmentioning
confidence: 99%
“…In Moebius syndrome and hypoglossia‐hypodactyly syndrome, histopathologic investigations of the brain stem [Govaert et al, 1989; Lipson et al, 1989; Gillerot et al, 1991; Lipson and Weaver, 1992; St Charles et al, 1993] and animal experimentation [Ranck and Windle, 1959; Lipson et al, 1989] indicated a role for vascular disruption in the pathogenesis of these conditions, and the term subclavian artery supply disruption sequence has been proposed [Bouwes Bavinck and Weaver, 1986].…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally associated malformations other than orofacial and limb defects have been observed in OLHS, including intestinal atresia [Nevin et al, 1980; David et al, 1992], unilateral renal agenesis [Johnson and Robinow, 1978], imperforate anus [Bersu et al, 1976] and hydrocephalus [Gillerot et al, 1991]. A few patients with pulmonary hypoplasia [Chicarilli and Polayes, 1985; Shechter et al, 1990; Maruyama and Koizumi, 2001] and a single female patient with gastroschisis [Kiliç et al, 2001] have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of this uncommon syndrome remains unknown and both environmental and genetic factors have been regarded (2). Estimated prevalence is 1:500.000 (1).…”
Section: Introductionmentioning
confidence: 99%